2014
DOI: 10.1016/j.dcn.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Positive parenting predicts the development of adolescent brain structure: A longitudinal study

Abstract: Little work has been conducted that examines the effects of positive environmental experiences on brain development to date. The aim of this study was to prospectively investigate the effects of positive (warm and supportive) maternal behavior on structural brain development during adolescence, using longitudinal structural MRI. Participants were 188 (92 female) adolescents, who were part of a longitudinal adolescent development study that involved mother-adolescent interactions and MRI scans at approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
160
1
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(181 citation statements)
references
References 73 publications
11
160
1
4
Order By: Relevance
“…Due to the design with only 1 measure of child brain volume, we cannot preclude reverse causality, but our findings are in accordance with recent experimental studies showing that parental sensitivity can result in differences in brain development in both infants and adolescents. 14,23 Several mechanisms may explain the association between parental sensitivity and child brain volume. First, early sensitive caregiving may reduce exposure to and experience of stress in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the design with only 1 measure of child brain volume, we cannot preclude reverse causality, but our findings are in accordance with recent experimental studies showing that parental sensitivity can result in differences in brain development in both infants and adolescents. 14,23 Several mechanisms may explain the association between parental sensitivity and child brain volume. First, early sensitive caregiving may reduce exposure to and experience of stress in children.…”
Section: Discussionmentioning
confidence: 99%
“…22 A recent study has demonstrated this mechanism in adolescents, showing that maternal sensitivity predicted reduced growth in the amygdala and greater thinning of the orbitofrontal cortex 4 years later. 23 Our study is a unique contribution to the literature in several ways. First, we examined the relation between early parenting and child brain structure in a large and relatively homogeneous sample of healthy children (N ¼ 191), thus extending previous results to nondisadvantaged families with fewer confounders.…”
mentioning
confidence: 97%
“…Because of these problems with identifying powerful and valid intervention targets, data that provide extra construct validity in terms of identifying potential causal pathways and mechanisms by which a risk factor might influence outcomes are particularly important. For example, previous recent research has shown that aspects of the family environment can influence brain development (Whittle et al, 2014) and immune functioning (Miller & Chen, 2010), both of which are plausible pathways to internalizing disorders, especially depression. Papers presented in this special section further extend the nomological network around parenting, providing extra construct validity for this risk factor by demonstrating that parenting predicts changes in brain function that can plausibly be related to risk mechanisms (Guyer et.…”
Section: Parenting As a Translational Developmental Neuroscience Intementioning
confidence: 99%
“…Cortical thickness is highly heritable (Goldman et al, 2009), with a complex relation with genetic background in schizophrenia (Blasi et al, 2013) and early experience (Whittle et al, 2014). Moreover, cortical thickness increases during normal neurodevelopment (Schmitt et al, 2014) and v) has been associated to treatment response (Szeszko et al, 2012) and cognition (Cassidy et al, 2014) in FE patients.…”
Section: Introductionmentioning
confidence: 98%